2013
DOI: 10.1136/amiajnl-2012-001510
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of traditional versus mobile app self-monitoring of physical activity and dietary intake among overweight adults participating in an mHealth weight loss program

Abstract: Objective Self-monitoring of physical activity (PA) and diet are key components of behavioral weight loss programs. The purpose of this study was to assess the relationship between diet (mobile app, website, or paper journal) and PA (mobile app vs no mobile app) self-monitoring and dietary and PA behaviors. Materials and methods This study is a post hoc analysis of a 6-month randomized weight loss trial among 96 overweight men and women (body mass index (BMI) 25-45 kg/m 2 ) conducted from 2010 to 2011. Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
292
3
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 346 publications
(312 citation statements)
references
References 24 publications
6
292
3
4
Order By: Relevance
“…Of 6 studies that compared combined interventions with conventional interventions, 4 reported significantly higher effect on adiposity in the combined intervention group. Of 5 RCTs evaluating combined interventions and diet, 3 found significant improvement in dietary intake 17, 18, 19, 20. Of 2 studies assessing combined interventions and conventional interventions, 1 reported significantly higher effect on diet in the combined intervention group and 1 reported no effect in either intervention group.…”
Section: Resultsmentioning
confidence: 99%
“…Of 6 studies that compared combined interventions with conventional interventions, 4 reported significantly higher effect on adiposity in the combined intervention group. Of 5 RCTs evaluating combined interventions and diet, 3 found significant improvement in dietary intake 17, 18, 19, 20. Of 2 studies assessing combined interventions and conventional interventions, 1 reported significantly higher effect on diet in the combined intervention group and 1 reported no effect in either intervention group.…”
Section: Resultsmentioning
confidence: 99%
“…For example, studies are mixed as to whether dietary tracking apps outperform traditional tracking strategies (i.e., paper and pencil) on measures of adherence and weight loss [3,4]. Another disconnect with the evidence base is that the behavioral strategies employed in apps have not been established as effective standalone interventions in their traditional forms.…”
Section: Do Mhealth Apps Work?mentioning
confidence: 99%
“…Two recent systematic reviews indicated that online social networks have been primarily used as an adjunct to in-person or web-based weight loss interventions, rather than as the primary treatment modality [18,19]. In previous studies, greater engagement in these online social networks predicted greater weight loss [20][21][22][23]. Thus, online social networks may represent an effective modality for delivering the entirety of an evidence-based weight loss program.…”
Section: Introductionmentioning
confidence: 99%